Building social capital in aquaculture: the case of northeastern Mexico - Dettmer González, Jorge (Universidad del Rosario, 2010)
The aim of this work is to identify some indicators of social capital in the sector of the aquaculture industry in the Northwest region of Mexico. Based on a theoretical model grounded in the social capital approach and network analysis, the article explores how social capital is being constructed in the aquaculture in Northwestern Mexico. Using a methodology that combines various documentary sources and information obtained from 48 interviews and 72 questionnaires applied to aquicultural SME, academic institutions and government agencies, this paper presents empirical evidence that suggests the existence of a social capital in construction in the mentioned region. It concludes that greater interaction between aquaculture producers, academia and government, could strengthen the existing social capital stock and, through this channel, contribute significantly to the development of this region.